Subjective well-being of Physical Education teachers during confinement in northern Mexico - Nuñez Enriquez, Oscar; González Rivas, Ramón Alfonso; Ramírez García, Adrián Alonso; Bibiano Mejia, Ma. Angeles; Alaniz Bernal, Cynthia Alejandra; Santos Sambrano, Gilberto (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The purpose of this research was to analyze the emotional state of physical education (PE) teachers in northern Mexico, from their educational supervisors and pedagogical supervisors (ATPs) perspective during confinement due to COVID-19. This was a descriptive and cross-sectional study with a qualitative approach of a phenomenological focus, three district supervisors and four technical-pedagogical advisers of Physical Education participated. Data collection was through focus groups and the analysis was collaborative and deductive-inductive from the perspective of subjective well-being. The main findings indicated that the teachers' emotional state influenced their professional performance. Two emotional states were identified: a) positive, related to happiness and enjoyment, due to the peacefulness of working from the comfort and safety of home; and b) negative, associated with stress and depression due to factors such as the death of relatives, friends and colleagues, and lack of contact with students. It was concluded that teachers' emotional state depends on their resilience or lack thereof; and educational authorities must develop strategies to support teachers' emotional care.